Pemanfaatan Internet of Thing Dalam Dunia Pendidikan Sekolah Menegah Atas Negeri 1 Kepahiang - Mardiana, Yessi; Kalsum, Toibah Umi; Prahasti, Prahasti; Sallaby, Achmad Fikri; Iskandar, Agung Pradana (Universitas Dehasen Bengkulu, 2024)
The relationship between technology and education has been going on for quite a long time. The use of information and communication technology for learning is increasingly developing. With the idea of ​​developing the internet of things (IoT), the use of technology for learning is increasingly showing significant progress. As a consequence, life activities are very dependent on the Internet, one of which is carrying out the education process. Considering the enormous potential for development of Internet of Things (IoT) technology, knowledge about this technology and how to use it in everyday life is very necessary. SMAN 1 Kepahyang has development potential in utilizing IoT technology, but requires training in its use in education. For this reason, the Faculty of Computer Science, Dehasen University, Bengkulu conducted community service regarding IoT technology to students at SMAN 1 Kepahyang. Material related to IoT is provided in stages from introduction to practical use of IoT in everyday life. The results of the training show that the students gained knowledge about how to use IoT in education